Comparative Genomic Analysis Reveals the Mechanism Driving the Diversification of Plastomic Structure in Taxaceae Species - Zhang, Yue; Xu, Yang; Chen, Hao; Wang, Liuyang; Yin, Kangquan; Du, Fang K. (Frontiers in Genetics, 2020)
Inverted repeat (IR) regions in the plastomes from land plants induce homologous recombination, generating isomeric plastomes. While the plastomes of Taxaceae species often lose one of the IR regions, considerable isomeric platomes were created in Taxaceae species with a hitherto unclarified mechanism. To investigate the detailed mechanism underpinning the IR-independent genesis of plastomic diversity, we sequenced four Taxaceae plastomes, including Taxus cuspidata Siebold & Zuccarini, Taxus fauna Nan Li & R. R. Mill and two individuals of Taxus wallichiana Zuccarini. Then we compared these structures with those of previously reported Taxaceae plastomes. Our analysis identified four distinct plastome forms that originated from the rearrangements of two IR-flanking inverted fragments. The presence of isomeric plastomes were then verified in T. cuspidata individuals. Both rearrangement analyses and phylogenetic results indicated that Taxaceae were separated into two clades, one including Taxus, Pseudotaxus and another formed by Amentotaxus and Torreya. Our reconstructed scenario suggests that the minimum number of inversion events required for the transformation of the plastome of Cephalotaxus oliveri Masters into the diversified Taxaceae plastomes ranged from three to six. To sum up, our study reveals a distinct pattern and the mechanism driving the structural diversification of Taxaceae plastomes, which will advance our understanding of the maintenance of plastomic diversity and complexity in conifers.